Routledge international handbook of social neuroendocrinology - Schultheiss, Oliver C. 1967-; Mehta, Pranjal H. 1977- (Routledge, 2019)
"The Routledge International Handbook of Social Neuroendocrinology is an authoritative reference work providing a balanced overview of current scholarship spanning the full breadth of the rapidly developing field of social neuroendocrinology. Considering the relationships between hormones, the brain, and social behavior, this collection brings together groundbreaking research in the field for the first time. Featuring 39 chapters written by leading researchers, the handbook offers impressive breadth of coverage. It begins with an overview of the history of social neuroendocrinology, before discussing its methodological foundations and challenges. Other topics covered include state-of-the-art research on dominance and aggression; social affiliation; reproduction and pair bonding (e.g., sexual behavior, sexual orientation, romantic relationships); pregnancy and parenting; stress and emotion; cognition and decision making; social development; and mental and physical health. The handbook adopts a lifespan approach to the study of social neuroendocrinology throughout, covering the role that hormones play during gestation, childhood, adolescence, and adulthood. It also illustrates the evolutionary forces that have shaped hormone-behavior associations across species, including research on humans, non-human primates, birds, and rodents. The handbook will serve as an authoritative reference work for researchers, students, and others intrigued by this topic, while also inspiring new lines of research on interactions among hormones, brain, and behavior in social contexts"--
Keywords: Human behavior / Endocrine aspects; Psychoneuroendocrinology